The impact of knowledge risk on sustainability of firms - Constantin Brătianu; Andrei Ștefan Neștian; Silviu Mihail Tiță; Ana Iolanda Vodă; Alexandra Luciana Guță (Amfiteatru Economic Journal, 2020)
The purpose of this paper is to investigate the impact of knowledge risk on the business sustainability of firms. In the knowledge economy, knowledge is a strategic resource of any firm, and it contributes significantly to the organizational performance and its competitive advantage. Knowledge risk is generated by knowledge absence, loss, leakage, spillover, and any other activity that induces uncertainty in decision-making. The present research focuses on the linkage between knowledge risk management and the firms' sustainability, having organizational performance as a mediating factor between knowledge risk and sustainability, and decision-making as a moderating factor between organizational performance and sustainability. The research integrates the qualitative approach based mostly on a critical analysis of the literature, and the quantitative approach based on designing a structural equation model and an associated questionnaire distributed online to a number of 1500 respondents from the business environment. Data obtained from the 299 valid questionnaires was processed by using STATA as a specialized program for statistical analysis and by using Structural Equation Modeling. The results confirm the structure of the research model and its associated hypotheses. Knowledge risk impacts firms' sustainability through the moderation of organizational performance. Decision-making impacts organizational performance and sustainability such that it acts as a moderating factor of the linkage between these constructs.
Keywords: C83; D83; Q01; 330; knowledge risk; sustainability; organizational performance; decision-making; risk management; knowledge management